1242The flexibility, ease of using, and leaving curve of a standardized ablation index workflow for catheter ablation of paroxysmal atrial fibrillation. (18th June 2020) - Gupta, D; Vijgen, J; De Potter, T; Scherr, D; Van Herendael, H; Knecht, S; Kobza, R; Berte, B; Sandgaard, N; Albenque, J; Szeplaki, G; Stevenhagen, Y; et al.
Abstract: Background/Introduction: The 'CLOSE' protocol, incorporating standardized ablation index (AI) targets in conjunction with defined inter-tag distance (ITD) has been shown to improve the acute and long-term success of pulmonary vein isolation (PVI) when treating paroxysmal atrial fibrillation (PAF). The reproducibility and learning curve for this protocol has not been studied. Purpose: To assess the acute and long-term efficacy of CLOSE PVI across multiple operators (n = 37) in the 17-centre European study 'VISTAX'. Methods: 329 patients with PAF (61.8% male, 61.3 ± 10.1 years) underwent PVI according to the CLOSE protocol, with target AI values for each lesion of ≥400 on the posterior wall and ≥550 on the anterior wall, and target ITD of ≤6mm. Each 3-dimensional electroanatomic map was evaluated at a core lab where adherence to each of these criteria was assessed. 281/329 patients (85.1%) fulfilled all standardized workflow requirements and were adjudicated as having their PVI per-protocol (PP). First pass PVI and acute effectiveness (adenosine-proof first pass PVI at 30-minute challenge) were recorded. Clinical effectiveness was assessed as freedom from atrial arrhythmia recurrence through 12 months recorded via transtelephonic monitoring (weekly and symptomatically), in addition to holter and electrocardiogram monitoring during 3, 6, 12 month follow up visits. Learning curve analysis was evaluated on all investigators. Results: First pass PVI rates were similar in the overall (86%) and PP cohorts (85%), as was acute effectiveness (82% in both cohorts). Freedom from atrial arrhythmia at 12 months too was identical for both cohorts (79%). Total procedure time and total ablation time decreased by an average 8 minutes and 10 minutes respectively after the first procedure and then showed further steady decreases over the number of ablations performed by the investigator (Figure). The procedural efficiencies and clinical success were reproducible across different centers. No significant deviations were found from individual sites. Conclusion: The standardized CLOSE workflow is reproducible across centres, and is 'forgiving' without impacting on high efficacy of almost 80%. The learning curve is short, suggesting that the excellent clinical results can be replicated widely and easily.